2020
DOI: 10.1186/s12890-020-01295-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical phenotypes and heath-related quality of life of COPD patients in a rural setting in Malaysia – a cross-sectional study

Abstract: Background The Spanish chronic obstructive pulmonary disease (COPD) guideline phenotypes patients according to the exacerbation frequency and COPD subtypes. In this study, we compared the patients’ health-related quality of life (HRQoL) according to their COPD phenotypes. Methods This was a cross-sectional study of COPD patients who attended the outpatient clinic of the Serian Divisional Hospital and Bau District Hospital from 23th January 2018 to 22th January 2019. The HRQoL was assessed using modified Medi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 42 publications
1
8
1
1
Order By: Relevance
“…The study of C. S. Chai in 2019 showed that patients with AE phenotype had a mean CAT score and a significantly higher proportion of patients with mMRC scores from 2-4, compared with ACO and NON-AE groups. The frequency of exacerbations in the ACO group in this study was also significantly smaller than that in the AE group [4]. The results in our study were also similar, specifically, the frequency of exacerbations of the ACO phenotype is significantly lower than that of the AE group.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The study of C. S. Chai in 2019 showed that patients with AE phenotype had a mean CAT score and a significantly higher proportion of patients with mMRC scores from 2-4, compared with ACO and NON-AE groups. The frequency of exacerbations in the ACO group in this study was also significantly smaller than that in the AE group [4]. The results in our study were also similar, specifically, the frequency of exacerbations of the ACO phenotype is significantly lower than that of the AE group.…”
Section: Discussionsupporting
confidence: 84%
“…The symptom severity based on mMRC and CAT scores of the NON-AE group in our study was lower than that in AE group, however, this difference was not statistically significant. Many studies on COPD phenotypes have shown significant differences in mMRC and CAT scores in the NON-AE group compared with the remaining phenotypes as studied by the authors H. Bao, C. S. Chai, and G. Reiger [1], [4], [11]. This could be explained by the small sample size of our study, which has not yet highlighted this difference.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…The baseline characteristics of the patients described in the included publications are presented in Supplementary Table 14 . Across the various GOLD group categorizations, the mean patient age at baseline ranged from 57.6 14 to 74.7 15 years (GOLD A), 59.1 14 to 77.9 15 years (GOLD B), 64.3 16 to 67.8 17 years (combined GOLD A/B), and 60.5 18 to 74.1 19 years (indirectly mapped combined GOLD A/B). The proportion of males ranged from 10.0% 20 to 98.3% 21 (GOLD A), 15.8% 22 to 96.5% 23 (GOLD B), 51.1% 16 to 61.1% 17 (combined GOLD A/B), and 52.1% 24 to 94.4% 25 (indirectly mapped combined GOLD A/B).…”
Section: Resultsmentioning
confidence: 99%
“…Forced expiratory volume in 1 second (FEV 1 ) % predicted ranged from 54.3% 32 to 83% 30 (GOLD A), 40% 33 to 72.8% 15 (GOLD B), and 43.6% 18 to 75.4% 25 (indirectly mapped combined GOLD A/B). One publication reported an FEV 1 % predicted of 57% among GOLD A/B patients 17 ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%